Asuhan Keperawatan Hipertermi Pada An. A Dengan Demam Typhoid di Ruang Soka RSUD Hj Anna Lasmanah Banjarnegara - Nur Indah Sarifah; Murniati M; Etika Dewi C (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Salmonella typhi is a bacterium that causes an acute infectious disease known as typhoid fever, which manifests as symptoms in the digestive tract. The endotoxin produced by these bacteria will increase local inflammation, disrupt the thermoregulation center, and cause hyperthermia. Typhoid fever in children usually begins with a fever that lasts for 7 days. Chills, dyspepsia, headaches, and an increase in body temperature to >37Â°C are other recognizable symptoms and signs of infection. The purpose of this research is to provide an overview of the nursing care given to An.A., who had typhoid fever, at Hj. Anna Lasmanah Hospital, Banjarnegara. The method used is a case study. The subject of this case study is An. A., aged 3 years. The results of the study were: red skin color, pale face, skin feeling warm, body temperature found to be 37.9 oC, and by examining Salmonella typhi O: 1/160 widal test. The intervention that was carried out was hyperthermic management by providing external cooling, namely onion compresses. Results of Case Study An. AÂ After nursing actions for 3 days, the problem was resolved with redness of the skin improving, not paleness, skin temperature improving, and body temperature decreasing to 36.9 oC. Conclusion: Red onion compresses can reduce body temperature in hyperthermic patients. Suggestion: Families can use onion compresses at home as a substitute for febrifuges.